84.8k views
2 votes
What is the solution to the following system of equations?

What is the solution to the following system of equations?-example-1
User Ashlei
by
5.4k points

2 Answers

4 votes
substitute y =6x - 11 into -2x - 3y = -7

-2x - 3y = -7
-2x - 3(6x - 11) = -7
-2x - 18x + 33 = -7
-20x = -40
x = 2

y = 6(2) - 11
y = 12 -11
y = 1

answer
D. (2, 1)
User Divyesh
by
4.7k points
6 votes

Answer:

The solution to the following system of equations is:

(2,1)

Explanation:

We have a system of equation as:


y=6x-11--------------(1)

and
-2x-3y=-7------------(2)

We solve following system of equation by the method of substitution.

We put the value of y in terms of x from equation (1) in equation (2)


-2x-3(6x-11)=-7\\\\\\i.e.\\\\\\-2x-18x+33=-7\\\\\\i.e.\\\\\\-20x+33=-7\\\\\\i.e.\\\\\\20x=33+7\\\\\\i.e.\\\\\\20x=40\\\\\\i.e.\\\\\\x=2

and now on putting the value of x back in equation (1) we get:


y=6* 2-11\\\\\\y=12-11\\\\\\y=1

The solution is: (2,1)

User Vivek Mishra
by
6.7k points